Legality of Release of Prisoners During the COVID-19 Pandemic in Positive Law Studies - Moch. Faizal Adi Wardana; Endah Lestari Dwirokhmeiti (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
When COVID-19 has been declared a National disaster, the Government of Indonesia assesses the need for fast action as an effort to save the community, prisoners and prisoners through assimilation and integration of the spread of the COVID-19 virus. Basically every prisoner is entitled to parole. Parole is the process of coaching prisoners outside prisons after serving at least 2/3 of the sentence from a minimum of nine months. So in essence, prisoners who are entitled to parole are those who have served 2/3 of their sentence. According to the Ministry of Law and Human Rights, the Assimilation and Integration program is also considered very helpful. Because in this way it can also help break the chain of spreading the COVID-19 virus. For prisoners who are released through assimilation and integration, they still receive supervision from the government. And for those who violate their assimilation will be revoked and given a harsher punishment.The general public already understands when they hear words such as prison, jail, detention center, and correctional facility and they really know who is the occupant of these places. Crime, murder, theft, robbery, rape, and so on are various types of criminal acts that make the perpetrators languish in them so that they get the title of prisoner at the end of their free period, or possibly get a higher level title, namely